2017
DOI: 10.3389/fpsyg.2017.02104
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Repetition as a Tool for Screening Morphosyntactic Abilities of Bilectal Children with SLI

Abstract: The clinical significance of sentence repetition tasks (SRTs) for assessing children's language ability is well-recognized. SRT has been identified as a good clinical marker for children with (specific) language impairment as it shows high diagnostic accuracy levels. Furthermore, qualitative analysis of repetition samples can provide information to be used for intervention protocols. Despite the fact that SRT is a familiar task in assessment batteries across several languages, it has not yet been measured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The task involves syntactic knowledge, language processing, memory and production (e.g., Polišenská et al 2015). SRep tasks are reliable tools for assessing typical and atypical language acquisition among different populations (Armon-Lotem and Meir 2016, Conti-Ramsden et al 2001, Marshall et al 2014, Theodorou et al 2017).…”
Section: Sentence Repetition As a Window For Children's Morphosyntactmentioning
confidence: 99%
“…The task involves syntactic knowledge, language processing, memory and production (e.g., Polišenská et al 2015). SRep tasks are reliable tools for assessing typical and atypical language acquisition among different populations (Armon-Lotem and Meir 2016, Conti-Ramsden et al 2001, Marshall et al 2014, Theodorou et al 2017).…”
Section: Sentence Repetition As a Window For Children's Morphosyntactmentioning
confidence: 99%
“…It has been recently shown that SRTs eliciting structures involving the latter operations can be reliably used to tease apart typically developing bilingual children from monolingual and bilingual children with SLI, not only in bilingual but also in bialectal settings (e.g., Armon-Lotem and Meir, 2016; Meir et al, 2016, 2017 for LITMUS-SRT in Russian and Hebrew; de Almeida et al, 2017; Fleckstein et al, 2018 for French; Lein et al, 2016; Abed Ibrahim and Hamann, 2017; Hamann et al, 2017; Hamann and Abed Ibrahim, 2017 for German; Theodorou et al (2017) for Cypriot-Greek; see also Marinis et al, 2017 for an overview). In particular, Armon-Lotem and Meir (2016) showed that although the highest level of diagnostic accuracy can be achieved using a combination of SRTs in the child’s L1/Russian and L2/Hebrew (applying bilingual cut-offs), good diagnostic accuracy can still be achieved if SRT is only administered in the societal language (L2-Hebrew).…”
Section: Introductionmentioning
confidence: 99%
“…Sentence Repetition tasks are widely used to assess morpho-syntactic abilities of monolingual and bilingual children. Sentence Repetition tasks have been shown to be highly effective in discriminating children with typical and atypical language development in monolingual and bilingual populations (e.g., Conti-Ramsden et al, 2001 ; Archibald and Joanisse, 2009 ; Klem et al, 2015 ; Meir et al, 2016 ; Antonijevic et al, 2017 ; Gavarró, 2017 ; Hamann and Abed Ibrahim, 2017 ; Theodorou et al, 2017 ; Fleckstein et al, 2018 ; among many others). In the following subsections, quantitative and qualitative characteristics of the Weaker Language of unbalanced bilinguals are discussed as compared to BB and unbalanced bilinguals in the Dominant Language.…”
Section: Introductionmentioning
confidence: 99%